Raising the Joint Line in TKA is Associated With Mid-flexion Laxity: A Study in Cadaver Knees. Issue 3 (March 2018) - Luyckx, Thomas; Vandenneucker, Hilde; Ing, Lennart Scheys; Vereecke, Evie; Ing, Arnout Victor; Victor, Jan
Abstract: Background: In a typical osteoarthritic knee with varus deformity, distal femoral resection based off the worn medial femoral condyle may result in an elevated joint line. In a setting of fixed flexion contracture, the surgeon may choose to resect additional distal femur to obtain extension, thus purposefully raising the joint line. However, the biomechanical effect of raising the joint line is not well recognized. Questions/purposes: (1) What is the effect of the level of the medial joint line (restored versus raised) on coronal plane stability of a TKA? (2) Does coronal alignment technique (mechanical axis versus kinematic technique) affect coronal plane stability of the knee? (3) Can the effect of medial joint-line elevation on coronal plane laxity be predicted by an analytical model? Methods: A TKA prosthesis was implanted in 10 fresh frozen nonarthritic cadaveric knees with restoration of the medial joint line at its original level (TKA0). Coronal plane stability was measured at 0°, 30°, 60°, 90°, and 120° flexion using a navigation system while applying an instrumented 9.8-Nm varus and valgus force moment. The joint line then was raised in two steps by recutting the distal and posterior femur by an extra 2 mm (TKA2) and 4 mm (TKA4), downsizing the femoral component and, respectively, adding a 2- and a 4-mm thicker insert. This was done with meticulous protection of the ligaments to avoid damage. Second, a simplified two-dimensional analytical model of the superficial medial collateral ligament (MCL) length based on a single flexion-extension axis was developed. The effect of raising the joint line on the length of the superficial MCL was simulated. Results: Despite that at 0° (2.2° ± 1.5° versus 2.3° ± 1.1° versus 2.5° ± 1.1°; p = 0.85) and 90° (7.5° ± 1.9° versus 9.0° ± 3.1° versus 9.0° ± 3.5°; p = 0.66), there was no difference in coronal plane laxity between the TKA0, TKA2, and TKA4 positions, increased laxity at 30° (4.8° ± 1.9° versus 7.9° ± 2.3° versus 10.2° ± 2.0°; p < 0.001) and 60° (5.7° ± 2.7° versus 8.8° ± 2.9° versus 11.3° ± 2.9°; p < 0.001) was observed when the medial joint line was raised 2 and 4 mm. At 30°, this corresponds to an average increase of 64% (3.1°; p < 0.01) in mid-flexion laxity with a 2-mm raised joint line and a 111% (5.4°; p < 0.01) increase with a 4-mm raised joint line compared with the 9-mm baseline resection. No differences in coronal alignment were found between the knees implanted with kinematic alignment versus mechanical alignment at any flexion angle. The analytical model was consistent with the cadaveric findings and showed lengthening of the superficial MCL in mid-flexion. Conclusions: Despite a well-balanced knee in full extension and at 90° flexion, increased mid-flexion laxity in the coronal plane was evident in the specimens where the joint line was raised. Clinical Relevance: When recutting the distal and posterior femur and downsizing the femoral component, surgeons should be aware that this action might increase the laxity in mid-flexion, even if the knee is stable at 0° and 90°.